Advancements in Homeopathic Research (Nov-Jan) 2019 (Advancements in Homeopathic Research, 2022)
50 well-diagnosed cases of PCOD have been short listed for this study from OPD record of Gaurang Clinic and Centre for Homoeopathic Research. In all cases, pre and post treatment pelvic ultrasound was done apart from detailed hormone analysis i.e. LH, FSH, Oestrogen, Progesterone, Prolactin, and Testosterone in a few cases. It was repeated in cases in which any one of them was found to be abnormal. Out of 50 patients treated with homoeopathic medicines, complete resolution of PCOD was achieved in 22 (44.00%), significant improvement in 6 (12.00%), 18 (36.00%) maintained status quo while 4 (8.00%) did not improve. Calcarea carbonica was the medicine of choice in maximum number of patients (24) but maximum response was obtained with Lycopodium. The statistical analysis of the data showed reduction in size of ovary, number and size of cysts.
Keywords: Oestrogen; Progesterone; Prolactin; Testosterone